2011
DOI: 10.1007/s12288-011-0107-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Thrombocytopenia in Pregnancy in Indian Women

Abstract: To find the prevalence and causes of thrombocytopenia during pregnancy. An analytical prospective observational study was conducted in Department of Obstetrics & Gynecology, CSMMU, Lucknow. 1079 antenatal women screened for thrombocytopenia and investigated for cause and management strategies and fetomaternal outcome were recorded. Prevalence of thrombocytopenia was 8.8%. Gestational thrombocytopenia was seen in 64.2%, obstetric in 22.1% and medical in 13.68% cases. Mean platelet count in controls was lower wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
39
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 18 publications
13
39
4
Order By: Relevance
“…The results of this study were consistent with our study findings. 18 In a study done in Ege University in Turkey assessing thrombocytopenia in pregnancy, around 43.5% of thrombocytopenia was due to HELLP syndrome followed by gestational thrombocytopenia (39.5%) and ITP was around 16%. 19 Fifty percent of patients were primigravida and 14% of patients had advanced maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were consistent with our study findings. 18 In a study done in Ege University in Turkey assessing thrombocytopenia in pregnancy, around 43.5% of thrombocytopenia was due to HELLP syndrome followed by gestational thrombocytopenia (39.5%) and ITP was around 16%. 19 Fifty percent of patients were primigravida and 14% of patients had advanced maternal age.…”
Section: Discussionmentioning
confidence: 99%
“…It may result in bleeding into mucous membranes presenting as petechiae, ecchymosed, epistaxis, gingival bleeding etc. Moreover, bruising, hematuria, gastrointestinal bleeding and rarely intracranial hemorrhage can occur 10 .…”
Section: Discussionmentioning
confidence: 99%
“…6 In our study majority of women had moderate thrombocytopenia (49%) at the time of delivery, 26% had severe thrombocytopenia and 25% had mild thrombocytopenia this is in contrast to other studies where they observed mild to moderate thrombocytopenia during delivery time. 2,5,9 The aim of management in these cases is to achieve and maintain a 'safe' rather than normal platelet count. An experienced team and an individualized approach are important.…”
Section: Fig 1: Severity Of Thrombocytopenia According To Etiologiesmentioning
confidence: 99%
“…1 The normal range of platelets in non-pregnant women is 150,000-400,000/µ L. Average platelet count in pregnancy is decreased 180,000-213,000 versus 250,000/µL. 2 Classification of thrombocytopenia in pregnancy is similar to non-pregnant patients. Mild thrombocytopenia is 100,000-150,000/µL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation